Safety and efficacy of cold‐water immersion in the treatment of older patients with heat stroke: a case series. Issue 1 (19th February 2021) - Ito, Chikao; Takahashi, Isao; Kasuya, Miyuki; Oe, Kyoji; Uchino, Masahito; Nosaka, Hideki; Sakamoto, So; Yoshida, Ryuhei; Kasuya, Satoshi; Fujimori, Daisuke; Nakamura, Satoshi; Yamada, Eri; et al.
Abstract : Background: Heat stroke treatment focuses on rapid cooling because symptom severity correlates with the duration of hyperthermia (i.e., time during which the core body temperature is sustained above the critical threshold). Several reports have revealed that cold‐water immersion is a safe and appropriate therapy for exertional heat stroke in young, otherwise healthy patients. However, few reports have assessed cold‐water immersion in older patients. We document three cases of cold‐water immersion in older heat stroke patients and evaluate its safety and efficacy. Case presentation: Three older patients with severe heat stroke were treated with cold‐water immersion. Core body temperatures decreased rapidly, and no complications occurred during the treatment. Conclusion: Cold‐water immersion can achieve rapid cooling and is effective in treating heat stroke. With special precautions, it can be performed safely for older patients. Further investigation is warranted to establish appropriate cooling methods in older adults. Abstract : Safety and efficacy of cold‐water immersion in the treatment of older patients with heat stroke.